Reliability assessment of MEMS devices - A case study of a 3 axis gyroscope - Makkonen, Joonas; Broas, Mikael; Li, Jue; Hokka, Jussi; Mattila, Toni T.; Paulasto-Krockel, Mervi (2012 4th Electronic System-Integration Technology Conference, 2012)
Recent technological breakthroughs in Micro-Electro-Mechanical Systems (MEMS) technologies have enabled significant cost reductions of MEMS gyroscopes and they are being increasingly employed in new application areas such as portable consumer electronics. Reliability assessment of MEMS assemblies is, however, more challenging than that of conventional IC assemblies: reliability characterization of MEMS must be made while the devices are in a functional state and the large number of small structural features requires new approaches for their physical failure analyses. In this paper we explore these challenges with a case study of MEMS gyroscopes, which are increasingly being employed in handheld consumer as well as automotive applications. Reliability of the gyroscopes will be characterized under elevated temperature and humidity (85°C/90%RH), and under high-G shock impact loading (up to 35 kG). The board assemblies were characterized for (i) maximum deceleration tolerance and (ii) fatigue lifetime under lower shock impact loads. Under the temperature-humidity characterization failures associated with absorption of moisture in the polymeric materials of the MEMS package showed early failures in 37 % of the samples while remainder of the samples survived 150 days of exposure. The shock impact characterization showed that the mean lifetime of the gyroscope assemblies depends significantly on the orientation of the impact load. Furthermore, package failures were produced at much higher decelerations (above 8 kG) than electrical failures of the device (at about 4 kG). Finite element model was established to predict the failure sites and the model correlated well with experimental observations. Several internal failure modes were e identified: fractured comb arms, fractured comb fingers, stuck MEMS elements, and chipped corners and edges of the elements caused by internal collisions. Transient failures were commonly observed under all testing conditions.